Potenciando la identificación del operario de limpieza con su organización: desarrollo de un plan piloto pedagógico en Grupo OL - Aspillaga Voysest, Andrea (2020)
This professional project exposes the work carried out by the authors in Grupo OL, an organization focused on providing comprehensive cleaning services, property maintenance and development of technological solutions to corporate clients, with the aim of achieving the formal incorporation of internal communication directed cleaning teams. The creation of the communications area had a positive impact on Human Resources management, providing the tools to meet collaborators in non-economic aspects, improve their quality of life and relationship with the company. The internal communication pilot plan, implemented in eight service units in Metropolitan Lima, allowed the cleaning workers to present a substantial improvement in the understanding of internal processes, regulations and benefits of their job. In the context of a difficult situation, training the leaders of each operating unit and having their support to transmit the information was the key to completing the project.